SUPPLY CHAIN DISRUPTION AND SUSTAINABILITY OF PHARMACEUTICAL FIRMS IN ANAMBRA STATE, NIGERIA - Eze, Solomon Uchehukwu (Milestone: Journal of Strategic Management, 2024)
The pharmaceutical sector, in Nigeria plays a role in the nations’ healthcare system by supplying medications to the people. However pharmaceutical companies in the Anambra State have been facing obstacles recently due to disruptions in their supply chains. This research investigates how supply chain disruptions impact the sustainability of firms in Anambra State. A mixed-methods approach, involving qualitative interviews with industry experts and quantitative analysis of operational data, identifies the main causes of supply chain disruptions and their effects on this firm’s long-term success. The research reveals that supply chain disruptions result from factors such as delays in customs clearance, inconsistent regulatory policies, currency fluctuations, inadequate transportation infrastructure and issues with supplier reliability. Interviews with industry experts highlighted customs delays as a disruption while quantitative analysis showed a 20% increase in times for imported pharmaceuticals along with a 15% rise in delivery delays and a 10% increase in product returns due to transportation challenges. Moreover, inefficiencies in inventory management were observed, leading to a 5% rise in holding costs and a 3% decrease in turnover rates due to supply chains. Challenges related to suppliers involved issues, with delivery reliability and product quality leading to a 10% extension in supplier lead times and a 5% uptick, in returns. The findings highlighted a direct correlation between these supply chain issues and decreased profitability, operational efficiency, and the ability to meet patient needs, emphasizing the urgent need for improvements to enhance the resilience of the pharmaceutical supply chain in Anambra State.